“Beings of secondary order”: Framing and intertextuality as narrative tools in A.S. Byatt’s “The Djinn in the Nightingale’s Eye” - Dobrogoszcz, Tomasz (Focus on events and narratives in language, psychology, social and medical practice, 2020)
Antonia Susan Byatt’s long-standing concern with the interaction between reality and art manifests in many of her texts. For instance, her most widely acclaimed novel, Possession, examines the postmodern preoccupation with the past and history through flagrant use of intertextuality and embedded tales. The story discussed in this paper, “The Djinn in the Nightingale’s Eye,” also employs the device of narrative framing in order to achieve metafictional aims. “The Djinn in the Nightingale’s Eye” is an exhibition of Chinese boxes: it engulfs the reader with stories built upon stories, tales descending into tales. Byatt achieves the effect of ontological flickering, Ingarden’s “iridescence,” by means of highlighting the constructed character of the embedded stories and, at the same time, placing the main plot line on the uncertain ground, as it slides between fairy tale and realist fiction, but does not decidedly advance towards magic realism. The insecurity of generic borders in “The Djinn in the Nightingale’s Eye” seems to illustrate Italo Calvino’s claim that “literature does not recognise Reality as such, but only levels.” Byatt’s protagonist is a narratologist, one of “beings of secondary order” who feed on stories and live by retelling tales. But she is also a self-reliant individual, who understands that the act of retelling “allows the teller to insert him- or herself into the tale.”